The Corelation Between Food Preferences and Nutritional Intake in Food Service at KH Mas Mansur Student Dormitory - Rizqillah, Dwi Rakhmawati; Muthmainah; Setyo Sri Rahardjo (Indonesian Nutrition Association, 2024)
Background Having good nutritional knowledge is not enough to form a healthy diet in students, it needs to be supported by a good consumption environment, such as food service in dormitories. Providing healthy food and having good preferences needs to be conducted to increase students' food intake. Objective The purpose of this study was to see how the correlation of food preferences in the dormitory with the amount of nutrient intake in students who lived in the KH dormitory Methods This study used an analytic observational design with a cross sectional approach. The subjects of this study were students who lived in dormitories with a total population of 365 students. Data collection was carried out by direct interview method with a 24-hour recall form instrumen for 3 days. Results The results of the correlation test showed that food preferences in the dormitory were positively correlated with total energy (p=0.032) and protein (p=0.012) intake. There was no correlation between food preferences in the dormitory with intake of fat and carbohydrate. Conclusions The higher the students' preference for food in the dormitory, the higher their energy and protein intake. So in this case, it is important for food organizers in the dormitory to further improve food preferences in the dormitory to provide better nutritional intake for students.